PNF in Practice An Illustrated Guide - Adler, Susan S.; Beckers, Dominiek; Buck, Math (Springer Berlin Heidelberg : Imprint: Springer, 2008)
PNF (Proprioceptive Neuromuscular Facilitation) is an approach to therapeutic exercise which therapists all over the world have found effective for treating patients with a wide range of diagnoses. The approach presented in this richly illustrated guide is based on the concepts set out by Dr. Herman Kabat and taught by Margaret Knott. The fully revised third edition demonstrates how the principles of the International Classification of Functioning, Disability and Health (ICF) and aspects of motor learning and motor control (from "hands-on" to "hands-off" management) are applied in modern PNF evaluation and treatment. The section on Activities of Daily Living has been expanded with new photos and more in-depth text instructions. A new fresh design and layout highlight the clearly structured way in which philosophy, basic procedures and treatment patterns of PNF are presented. Thus, this textbook provides a systematic and easily accessible guide to learning and understanding PNF as a practical tool and using it to full effect in patient treatment.